Testing the boundaries: Seasonal residency and inter-annual site fidelity of basking sharks in a proposed Marine Protected Area. (May 2017) - Doherty, P.D.; Baxter, J.M.; Godley, B.J.; Graham, R.T.; Hall, G.; Hall, J.; Hawkes, L.A.; Henderson, S.M.; Johnson, L.; Speedie, C.; Witt, M.J.
Abstract: There is a growing need to understand the inter-annual movements of mobile marine species of conservation concern to inform the design and placement of Marine Protected Areas (MPAs) to maximise their conservation potential. We use satellite telemetry data from 36 basking sharks ( Cetorhinus maximus ) tracked in 2012, 2013 and 2014 (cumulative total: 1598 days; median: 44 days; range: 10–87 days) to quantify movements in coastal waters off the west coast of Scotland within the Sea of the Hebrides proposed MPA. Sharks exhibited seasonal residency to the proposed MPA, with a mean of 84% of filtered best daily locations occurring within its boundaries (2012 = 80%, 2013 = 90% and 2014 = 74%). Three long-term tracked basking sharks demonstrated inter-annual site fidelity, returning to the same coastal waters in the year following tag deployment, with two returning to within the boundaries of the proposed MPA. These data likely suggest the area experiences favourable conditions and/or resources for basking sharks across years and, if designated, coupled with appropriate management, could afford protection during summer months. Highlights: Testing of a MPA prior to designation, a process not often afforded to most MPAs High levels of residency, with > 90% overlap between core activity areas and the MPA Inter-annual site fidelity of individuals to the area, showing year-round migration Study area likely provides conditions for key life history events to occur